The dynamic microenvironment of pancreatic islet cell transplants precludes the use of common housekeeping genes. (1st January 2014) - Shahaf, Galit; Kassem, Ali; Levinson, Justin B.; Brazg, Jared M.; Lewis, Eli C.
Background: Pancreatic islet graft survival is affected by early (<3 days) and late immune responses, displaying local CD3+ T cell predominance and loss of insulin production within a week. However, qRT–PCR gene expression profiles require normalisation to housekeeping genes that might be affected by metabolic, inflammatory, hypoxic, apoptotic, revascularisation–related and immune–cell infiltrate changes. Here, we examined eight housekeeping genes. Methods: Syngeneic and allogeneic mouse islet transplantations were performed; day 1 and 7 grafts were analysed for insulin and CD3 transcript levels, as normalised to each housekeeping gene. Results: Normalised qRT–PCR data was not uniform across transplant combinations and time from transplantation. 18s RNA was the superior housekeeping gene, as confirmed by valid changes in CD3 and insulin expression levels. Conclusions: While β–actin and GAPDH are the least–fitting housekeeping genes for the dynamic microenvironment of islet transplants, 18s RNA maintains authenticity across transplant combinations, time from transplantation and altered immune microenvironment.